Epithermal fluids evolution related to an IOCG system in Cerro Colorado Chico - Bazan Santa Cruz, Orlando (2023)
Cerro Colorado Chico located in Ancash region, northern coast of Peru. Brecciated siliceous bodies occur with restricted halos of advanced argillic alteration silica-pyrophyllite-alunite and extensive silica-sericite-pyrite alteration, breccias and hematite bodies, hematitized horizons into volcano-sedimentary rocks of the Casma Group. A microthermometry study of fluid inclusions has been carried out in 4 samples with a total of 55 primary and secondary fluid inclusions in quartz. Two stages are distinguished, the first at mesothermal temperatures between 605° and 560° C with salinities of 47.66% to 44.82% NaCl eq., and the second at epithermal temperatures between 329° and 138° C with salinities of 0.7%. to 9.73% NaCl eq., with complex fluids evolution processes as cooling, dilution, mixing and boiling. This study permit to explain the processes that take place in the epithermal environment of IOCG-type magmatic-hydrothermal systems from fluids derived of silica-rich silicate melts that partition from poorly differentiated magmas, when decompressed separate into a dense saline liquid phase and a low-density vapor phase that rises to the upper levels and is responsible for the formation of the brecciated siliceous bodies and the advanced argillic alteration.